Full-crystalline mordenite formed catalyst as well as preparation method and application thereof
The preparation of fully crystalline mordenite zeolite shaped catalysts by steam-assisted crystallization solves the problems of complex preparation processes and environmental pollution in existing technologies, and realizes efficient and green catalyst production that meets the mechanical strength and catalytic performance requirements of industrial applications.
Patent Information
- Application Number
- CN202511642955.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-11
- Publication Date
- 2026-02-03
AI Technical Summary
Existing fully crystalline mordenite zeolite molding catalysts have complex preparation processes, low production efficiency, and serious environmental pollution, making it difficult to meet the mechanical strength and catalytic performance requirements for industrial applications.
A fully crystalline mordenite zeolite-shaped catalyst was prepared by steam-assisted crystallization. The binder was converted into a molecular sieve through secondary crystallization, avoiding contact with the liquid phase, simplifying the preparation process, reducing the use of organic template agents, and shortening the crystallization time.
It significantly improves the content of active components and mechanical strength of the catalyst, optimizes mass transfer performance, reduces production costs and environmental pollution, and is suitable for industrial-scale production.
Smart Images

Figure CN121446535A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of chemical catalysis, and particularly relates to a full-crystalline mordenite shaped catalyst, a preparation method thereof and an application of the full-crystalline mordenite shaped catalyst in a methanol / dimethyl ether carbonylation reaction. BACKGROUND
[0002] Ethanol, as an important clean energy, can promote the diversification of energy structure and improve air quality, and help green and sustainable development. With the increasing global demand for energy and the proposal of the "double carbon" target, developing efficient and low-carbon ethanol production processes has become a research hotspot. Starting from coal-to-syngas, through methanol / dimethyl ether carbonylation to acetic acid / methyl acetate, and then hydrogenation to ethanol, is a new process route. It has the advantages of strong atom economy, high product selectivity, mild reaction conditions, etc., and meets the strategic needs of energy structure transformation and low-carbon development in China, and has broad industrial application prospects.
[0003] In this process route, the carbonylation reaction is the core step. Mordenite catalysts have become the current industrial catalysts due to their good initial activity and high selectivity. In the existing process, the reaction is carried out in a fixed bed at medium-high pressure (2.5-4.5 MPa), which puts high requirements on the mechanical strength of the catalyst. Catalyst shaping is a key link to ensure mechanical strength and avoid high bed pressure drop. However, the introduction of a large amount of inert binder (10-40 wt.%) during the shaping process greatly reduces the content of active components when loading the same volume or mass of catalyst. At the same time, the binder can also block the microporous channels of the molecular sieve, limiting mass transfer and thus reducing catalytic performance. Therefore, eliminating the negative effects of the binder is the key to ensuring the efficiency of the shaped catalyst.
[0004] Full-crystalline molecular sieve shaped catalysts are composed entirely of molecular sieve crystals and do not contain inert components, fundamentally avoiding the problems of active component dilution and pore blockage. The main preparation paths include one-pot hydrothermal synthesis and conversion of the binder into a molecular sieve through secondary crystallization (such as the research of Liu Zhongmin, Wang Yaqun, et al. (ACS Appl. Mater. Interfaces 2018, 10, 32239-32246; Mater. Chem. Phys. 2022, 292, 126823) and existing patent technologies such as CN201410428790.3, CN202410310893.3). Although the full-crystalline strategy can effectively solve the negative effects of the binder, its industrial application still faces many challenges: one-pot hydrothermal synthesis often has poor shape stability and insufficient mechanical strength, and the post-synthesis secondary conversion process is complex, long, and uses a large amount of organic template, which is low in production efficiency, not conducive to scale-up production, and leads to a large amount of nitrogen-containing wastewater and waste gas emissions.
[0005] Therefore, developing a simple, green and efficient preparation method of full crystalline mordenite shaped catalyst can not only improve the technical competitiveness of methanol / dimethyl ether carbonylation synthesis reaction and even synthesis gas to ethanol process, but also has important enlightenment and guidance significance for the development of molecular sieve catalysts and green production technology in petrochemical and chemical industry. SUMMARY
[0006] The present application aims at the problems of complex process, low production efficiency and environmental pollution in the current preparation technology of shaped molecular sieve, and provides a full crystalline mordenite shaped catalyst, a preparation method and application thereof. The method adopts mordenite, a binder (silicon source, aluminum source and alkali) to form a shape, and then prepares by steam assisted crystallization; the binder is converted into molecular sieve by secondary crystallization; in the steam assisted crystallization process, the molecular sieve does not contact with the solution, so that the preparation of full crystalline mordenite shaped catalyst is realized. The present application is simple, green, efficient and easy to scale up, and can successfully prepare full crystalline molecular sieve in a very short crystallization time without using organic template agent.
[0007] The technical scheme of the present application is as follows: A full crystalline mordenite shaped catalyst, which is entirely composed of mordenite crystals and does not contain other crystalline or amorphous components, has a mechanical strength of 60-300 N / cm, and a shape of spherical, strip, trilobate, etc., which are commonly used in industrial catalysts, a diameter of 1-5 mm, and a length of 1-10 mm.
[0008] The preparation method of the full crystalline mordenite shaped catalyst comprises the following steps: (1) mixing a silicon source, an aluminum source, an alkali source and water to form a white colloid, and then mixing the colloid with mordenite molecular sieve to form a shape to obtain a catalyst precursor; wherein the molar ratio of the silicon source, the aluminum source, the alkali source and water is 1:(0.025-0.25):(0.05-0.5):(5-30); the content of the molecular sieve is 50-90 wt% of the total mass of the precursor; and the molar amount of the silicon source is calculated based on silicon dioxide; The silicon source is selected from one or more of silica sol, sodium silicate and water glass; the aluminum source is selected from one or more of aluminum sulfate, aluminum nitrate and sodium metaaluminate; the alkali source is sodium hydroxide; and the molecular sieve is selected from mordenite.
[0009] The shaping can adopt typical extrusion shaping, and the specific steps are as follows: the colloid is added dropwise into the molecular sieve powder, kneading is continuously performed during the adding process to obtain a wet material mass; the wet material mass is sent into an extruder to extrude a strip-shaped material through a die; after drying at room temperature, the strip-shaped material is cut into cylindrical particles, and then dried at 100-120 DEG C for 10-12 hours to obtain the catalyst precursor.
[0010] (2) the catalyst precursor is loaded on a grid in a crystallization kettle, water is added at the bottom, and then sealed, and steam assisted crystallization is carried out at 150-200 DEG C for 0.5-72 h; after crystallization, the sample is washed, dried and calcined to obtain a Na-type mordenite shaped catalyst; The mass ratio of the catalyst precursor to water is 1:1-1:5. (3) the Na-type mordenite shaped catalyst is immersed in an ammonium salt solution, and after ammonium ion exchange, the sample is filtered, washed, dried, and calcined at 400-600 DEG C in an air atmosphere for 3-8 h to obtain a hydrogen-type fully crystalline mordenite shaped catalyst; The ammonium salt is one or more of ammonium nitrate, ammonium chloride, ammonium carbonate and ammonium sulfate, and the concentration of the ammonium salt is 0.1-1 mol / L; the exchange temperature is room temperature-80 DEG C, and the exchange time is 1-8 h. The diameter of the catalyst precursor in step (1) is 1-5 mm, and the length is 1-10 mm. In step (2), the solid is washed to pH<9 after crystallization, dried, and calcined at 500-600 DEG C in an air atmosphere for 3-8 h.
[0011] The application of the fully crystalline mordenite shaped catalyst is used for synthesizing methyl acetate from dimethyl ether carbonylation or synthesizing acetic acid from methanol carbonylation.
[0012] Specifically includes the following steps: The raw material gas, carbon monoxide and auxiliary gas are introduced into a fixed bed reactor under the conditions of 180-260 DEG C, a pressure of 1.0-5.0 MPa, and a total space velocity of 1500-12000 h -1 to obtain the product; The molar fraction of each component in the total material is: 2-20% raw material gas, 60-98% carbon monoxide, and 0-20% auxiliary gas; when the proportion is 0, it means that the material is not added; the raw material is dimethyl ether or methanol; When the raw material is dimethyl ether, the product is methyl acetate; when the raw material is methanol, the product is acetic acid; The auxiliary gas is hydrogen or an inert gas; the inert gas is nitrogen, argon or helium.
[0013] The substantial features of the present application are: Compared with the one-step hydrothermal synthesis method in the prior art, the secondary crystallization strategy adopted in the application can realize flexible regulation of the shape and size of the shaped catalyst, avoids the operation of vacuum adsorption in ACS Appl. Mater. Interfaces 2018, 10, 32239-32246 and the dependence on various complex silicon sources and templates in CN201410428790.3, significantly simplifies the raw material system and reduces the cost. In terms of the core crystallization process, the steam-assisted crystallization method adopted in the patent can ensure that the shaped catalyst does not directly contact with the liquid phase, avoiding the collapse of the macrostructure and the decrease of the mechanical strength of the catalyst caused by the use of traditional hydrothermal synthesis (which requires the shaped catalyst to be immersed in the solution) in Mater. Chem. Phys. 2022, 292, 126823 and CN201410428790.3. At the same time, this method can completely abandon the use of organic templates and eliminate the generation of nitrogen-containing wastewater, making the whole process more green and environmentally friendly. In addition, the crystallization time of the patent is greatly shortened from 72 hours reported in the literature to 12 hours, which significantly improves the synthesis efficiency.
[0014] Compared with the prior art, the application has the following beneficial effects: The full-crystalline mordenite shaped catalyst prepared by the application does not contain inert components, significantly increases the content of active components and the number of active sites in the shaped catalyst, and eliminates the problem of pore blockage caused by the binder in conventional shaping, has better mass transfer performance, and has potential advantages of molecular sieves in the fields of adsorption and catalysis.
[0015] The preparation method of the application realizes synchronous improvement of reaction performance and mechanical strength. Experimental data show that the reaction performance of the shaped catalyst (Example 1) prepared by the application is better than that of Comparative Example 4 (mordenite raw powder) and Comparative Example 5 (mordenite shaped catalyst prepared by using pseudoboehmite as a binder). Under the same reaction conditions, the dimethyl ether conversion rate of Comparative Example 4 is 72.2%, the dimethyl ether conversion rate of Comparative Example 5 is 54.7%, and the dimethyl ether conversion rate of Example 1 is 87.4%. The conversion rate of the example is increased by 21% and 54% compared with Comparative Examples 4 and 5, respectively. At the same time, the average mechanical strength of Comparative Example 5 is 112.3 N / cm, and the average mechanical strength of Example 1 is 131.8 N / cm, which is increased by 17% compared with Comparative Example 5.
[0016] The preparation method has excellent process adaptability, and can successfully synthesize full-crystalline mordenite formed catalyst with high catalytic performance and mechanical strength in a wide parameter range. By systematically regulating the key parameters such as silicon-aluminum ratio (4-10), alkalinity (NaOH / SiO2=0.05-0.4), mordenite content (60-90 wt%), template dosage (0-16 wt%) and crystallization time (0.5-72 h), the formed catalyst with good crystallinity, stable dimethyl ether conversion rate and mechanical strength meeting the standards can be obtained. The characteristics show that the method has strong process fault tolerance and operation flexibility, which provides an important guarantee for coping with raw material fluctuation and process fine-tuning in the industrialization amplification process.
[0017] The preparation method is green and environmentally friendly, and meets the green development strategy of China. In the absence of a template, a formed catalyst with excellent catalytic performance and mechanical strength (Example 11) can still be synthesized, with a dimethyl ether conversion rate of 86.6% and an average mechanical strength of 129.4 N / cm. The performance is similar to that of Example 1, and better than that of Comparative Example 4 and Comparative Example 5. Therefore, the large amount of wastewater and exhaust gas generated in the production process of molecular sieves is avoided, which has significant economic and environmental benefits.
[0018] The preparation method has high synthesis efficiency and is suitable for large-scale production. The dimethyl ether conversion rate of the obtained catalyst can reach 82.4% only after 3 h of crystallization, which is similar to that of the sample crystallized for 72 h (Example 11), and higher than that of the molecular sieve raw powder (Comparative Example 4); after the crystallization time is extended to 12 h, the average mechanical strength reaches 112.3 N / cm, which is comparable to the traditional industrial formed catalyst (Comparative Example 5), meeting the requirements of industrial fixed-bed reactors for catalyst strength.
[0019] The preparation process of the full-crystalline mordenite formed catalyst is simple, green, efficient, the raw materials are widely available and relatively low in price, which is conducive to large-scale industrial production. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 The X-ray diffraction pattern of the sample in Example 1.
[0021] Figure 2 The catalytic performance diagram of the sample in Example 1.
[0022] Figure 3 The photo of the sample in Example 1.
[0023] Figure 4 The photo of the sample in Comparative Example 1.
[0024] Figure 5 The photo of the sample in Comparative Example 2.
[0025] Figure 6 Scanning electron microscope image of the sample of Example 1.
[0026] Figure 7 Scanning electron microscope image of the sample of Comparative Example 3.
[0027] Figure 8 Scanning electron microscope image of the sample of Comparative Example 5. DETAILED DESCRIPTION
[0028] The application will be further described in conjunction with the specific embodiments and the accompanying drawings. It should be noted that the following examples are illustrative and are not intended to limit the scope of the present application. The raw materials required in the following examples and comparative examples are commercially available.
[0029] In the present embodiment, the crystal structure of the sample was analyzed using a Rigaku MiniFlex 600 powder X-ray diffractometer from Rigaku Corporation, Japan. The test conditions were as follows: the diffraction source was Cu Kα ray (λ = 1.54056 Å), the working voltage was 40 kV, the working current was 200 mA, the scanning range was 5-50°, and the scanning speed was 8° / min. The relative crystallinity of the sample was calculated based on the sum of the peak areas of the XRD diffraction peaks corresponding to the (200), (330), (150), (202), and (350) crystal planes, and the crystallinity of Comparative Example 4 was taken as 100% as a reference, and the relative crystallinity of other samples was determined by the ratio of the sum of the peak areas to the reference.
[0030] In the present embodiment, the morphology analysis of the sample was observed using an Apreo SLoVac scanning electron microscope from Thermo Fisher Scientific.
[0031] In the present embodiment, the mechanical strength of the shaped catalyst was tested on a ZQJ-Ⅱ intelligent particle strength tester from Dalian Intelligent Tester Factory. During the test, the shaped catalyst was placed on the sample stage, and a continuous pressure was applied to the side surface until the particle was broken, and the pressure value at the moment of breaking was recorded. The crushing strength was calculated from the ratio of the breaking pressure to the length of the particle. At least 50 shaped catalysts with a length of 3-5 mm were selected from each sample as samples, and the average value of the test results was taken as the index of the quantitative mechanical strength of the shaped catalyst.
[0032] Example 1: 10.6 g of 30 wt% silica sol (i.e., 53 mmol of silicon dioxide), 0.44 g of sodium hydroxide (11 mmol), and 0.82 g of sodium aluminate (10 mmol) were mixed evenly to obtain a white, homogeneous colloid. This colloid was added dropwise to 16 g of mordenite molecular sieve powder, with continuous kneading during the addition process to ensure thorough mixing of the colloid and molecular sieve, forming a wet agglomerate suitable for extrusion. The wet agglomerate was fed into an extruder and extruded through a die to form strips with a diameter of 2 mm. After drying at room temperature for 6 h, the strips were cut into cylindrical particles 3–5 mm in length and then dried in a drying oven at 110 ℃ for 12 h to obtain the catalyst precursor.
[0033] Six g of catalyst precursor was added to the grid in a 200 mL crystallization reactor, and 12 g of tetraethylammonium hydroxide aqueous solution (4 wt%) was added to the bottom of the reactor before sealing. The reactor was heated at 170 °C for 72 h. After crystallization, the solid product was collected by filtration, washed with water until the pH of the filtrate was <9, and then dried overnight at 110 °C. The dried sample was calcined at 550 °C in air for 5 h to obtain Na-type mordenite zeolite. It was mixed with 150 mL of 0.5 mol / L ammonium sulfate aqueous solution and stirred at 80 °C for 6 h for ion exchange. After ion exchange, it was filtered, washed, dried, and then calcined at 520 °C in air for 4 h to finally obtain the hydrogen-form fully crystalline mordenite zeolite shaped catalyst.
[0034] The obtained XRD patterns of the samples are attached. Figure 1 As shown. No other impurity phases were formed after steam-assisted crystallization. (See attached image.) Figure 3 and 6 As shown, the catalyst appears as white cylindrical particles, intact and without breakage. The cross-section reveals that the grains are tightly bonded, forming a complete and dense overall structure. This structure originates from the new molecular sieve crystals generated by the conversion of the binder, which act as a "bridge," tightly cross-linking the particles and thus constructing a robust catalyst.
[0035] Take 0.33 g of the crushed and sieved catalyst sample (40-60 mesh) and test it under the following conditions: total pressure 1.5 MPa, 200℃, feed gas composition (mole fraction) of 2% dimethyl ether and 98% carbon monoxide, and total space velocity 9000 h⁻¹. -1 The reaction was carried out in a fixed-bed reactor (reaction tube inner diameter 8 mm, length 850 mm). Before the reaction, the catalyst was purged in situ with high-purity nitrogen for 6 h. The reaction tail gas was analyzed by online gas chromatography under controlled temperature. The activity and selectivity results for the synthesis of methyl acetate from dimethyl ether carbonylation of the sample are attached. Figure 2 As shown.
[0036] Comparative Example 1: While maintaining the same conditions as in Example 1, this comparative example employed a hydrothermal synthesis strategy. Specifically, the catalyst precursor was immersed in a tetraethylammonium hydroxide aqueous solution (4 wt%) and crystallized at 170°C for 72 h. (See attached...) Figure 4 As shown, the obtained sample exhibited significant fragmentation and lacked industrial application value. This is attributed to the instability of the binder in the alkaline solution, leading to its dissolution and ultimately structural destruction. Therefore, the hydrothermal synthesis method is not suitable for the preparation of fully crystalline molecular sieves.
[0037] Comparative Example 2: With all other conditions remaining the same as in Example 1, the aluminum source was replaced with boehmite. (See attached...) Figure 5 As shown, although the obtained sample retains its original shape, its surface exhibits numerous macroscopic defects such as pores, which are detrimental to industrial applications. This is attributed to the slow dissolution of boehmite, making it difficult to provide sufficient aluminum source for crystallization and thus inhibiting the crystallization process. Simultaneously, a large amount of unconverted silica is unstable under alkaline conditions, leading to localized dissolution and the formation of macroscopic defects. Therefore, boehmite is unsuitable as an aluminum source for preparing fully crystalline molecular sieves.
[0038] Comparative Example 3: Under the same conditions as in Example 1, this comparative example did not undergo steam-assisted crystallization treatment. (See attached...) Figure 7 As shown, the cross-sectional morphology of the obtained sample shows a state of particle accumulation, but compared with Example 1, the degree of bonding between particles is weaker and the overall structure is poorer.
[0039] Comparative Example 4: This comparative example is an H-type powder sample obtained by directly ion exchange and calcining the mordenite powder used in the molding process of Example 1 without molding treatment.
[0040] Comparative Example 5: 10 g of ammonium-type mordenite powder, 3.18 g of pseudoboehmite, and 0.25 g of guar gum powder were uniformly mixed. Then, 0.15 g of HNO3 and 8.2 g of H2O were added dropwise to the powder mixture, continuously kneading during the addition process to ensure thorough mixing and form a wet agglomerate suitable for extrusion. This wet agglomerate was fed into an extruder and extruded through a specific die into strips with a diameter of 2 mm. After drying at room temperature for 6 h, it was cut into cylindrical particles 3–5 mm in length, transferred to an oven at 110 ℃ and dried for 12 h, and finally calcined at 520 ℃ in air for 4 h to obtain the comparative catalyst. The morphology of the sample is shown in the attached figure. Figure 8 The cross-sectional morphology of the sample shows a particle-packed structure, with the particles tightly connected by a binder.
[0041] The physical properties and reaction performances of different samples are shown in Table 1. Due to the dilution of active components caused by the introduction of the binder, the relative crystallinity of Comparative Examples 3 and 5 decreases to 76% and 82%, respectively. After steam-assisted crystallization, the relative crystallinity of Example 1 increases to 98%, which is similar to that of Comparative Example 4 (powder catalyst). The activity results show that the dimethyl ether conversion rate of Example 1 reaches 87.4%, which is much higher than that of Comparative Examples 3 (34.7%) and 5 (54.7%), and even higher than that of Comparative Example 4 (powder catalyst, 72.2%). At the same time, the mechanical strength of Example 1 is higher than that of Comparative Examples 3 and 5, indicating that it has good mechanical properties while maintaining high activity. The above results fully demonstrate that the fully crystalline mordenite shaped catalyst prepared by the present application has excellent dimethyl ether carbonylation reaction performance and mechanical strength that meets the requirements of industrial applications.
[0042] Table 1 Relative crystallinity, dimethyl ether carbonylation reaction performance and mechanical strength of different samples
[0043] Examples 2-4: Under the condition that other conditions are completely the same as those of Example 1, only the silicon-aluminum ratio of the raw material is changed to 10 (Example 2), 8 (Example 3), and 4 (Example 4) to explore the influence of the silicon-aluminum ratio on the performance of the catalyst.
[0044] Table 2 lists the relative crystallinity, catalytic performance and mechanical strength test results of different silicon-aluminum ratio samples. Studies have shown that the silicon-aluminum ratio has no significant effect on the relative crystallinity and mechanical strength of the sample. However, the silicon-aluminum ratio shows a clear "volcano-type" change rule on the dimethyl ether carbonylation activity: with the decrease of the silicon-aluminum ratio, the catalytic activity first increases and then decreases, and reaches a peak when the silicon-aluminum ratio is 6 (Example 1), obtaining the highest dimethyl ether conversion rate.
[0045] Table 2 Relative crystallinity, dimethyl ether carbonylation reaction performance and mechanical strength of different silicon-aluminum ratio samples
[0046] Examples 5-7: Under the condition that other conditions are completely the same as those of Example 1, only the ratio of sodium hydroxide and silicon dioxide in the raw material is changed to 0.05 (Example 5), 0.1 (Example 6), and 0.4 (Example 7) to systematically investigate the influence of alkalinity on the performance of the catalyst.
[0047] Table 3 lists the relative crystallinity, catalytic performance and mechanical strength data of samples with different alkali contents. The study shows that the change of alkali content has no significant effect on the relative crystallinity and dimethyl ether carbonylation activity of the samples within the test range. However, with the increase of alkali content, the mechanical strength of the shaped catalyst shows a clear upward trend, indicating that a high alkaline environment helps to enhance the overall structural stability of the catalyst.
[0048] Table 3 Relative crystallinity, catalytic performance of dimethyl ether carbonylation reaction and mechanical strength of samples with different alkali contents
[0049] Examples 8~10: Under the condition that other conditions are exactly the same as in Example 1, only the mordenite content during shaping is changed to 90 wt% (Example 8), 70 wt% (Example 9), and 60 wt% (Example 10), and the effect of mordenite content on the comprehensive performance of the catalyst is investigated.
[0050] Table 4 lists the relative crystallinity, catalytic performance and mechanical strength data of samples with different mordenite contents. With the change of mordenite content, the relative crystallinity, dimethyl ether conversion rate and mechanical strength of the samples all show a trend of first rising and then falling. When the mordenite addition amount is 80 wt% (Example 1), the performance indicators all reach the optimal value. This result shows that a suitable mordenite content plays a key role in maintaining the high crystallinity, excellent catalytic activity and good mechanical strength of the catalyst, and too high or too low content will lead to performance decline.
[0051] Table 4 Relative crystallinity, catalytic performance of dimethyl ether carbonylation reaction and mechanical strength of samples with different mordenite contents
[0052] Examples 11~13: Under the condition that other conditions are exactly the same as in Example 1, only the content of tetraethylammonium hydroxide is changed to 0 wt% (Example 11), 10 wt% (Example 12), and 16 wt% (Example 13), and the influence law of template dosage on the performance of the catalyst is investigated.
[0053] Table 5 lists the relative crystallinity, catalytic performance and mechanical strength data of the samples with different template contents. Adjusting the template content has no obvious effect on the relative crystallinity and dimethyl ether carbonylation activity of the samples, and the dimethyl ether conversion rate of each example remains stable. It is worth noting that under the condition of not adding any template (Example 11), a fully crystalline mordenite shaped catalyst with excellent dimethyl ether carbonylation activity and relatively high mechanical strength is still successfully prepared, and its performance is comparable to that of the sample using a template. This finding shows that the present method effectively avoids the use of organic templates while maintaining the catalytic performance, in line with the concept of green synthesis, and provides an important technical advantage for industrialization.
[0054] Table 5 Relative crystallinity, catalytic performance of dimethyl ether carbonylation reaction and mechanical strength of samples with different template contents
[0055] Examples 14-16: Under the condition that all other conditions are exactly the same as in Example 11, only the crystallization time is changed to 1 h (Example 14), 3 h (Example 15), and 12 h (Example 16), and the effect of crystallization time on catalyst performance is systematically studied.
[0056] Table 6 lists the relative crystallinity, catalytic performance and mechanical strength data of the samples with different crystallization times. With the extension of the crystallization time, the relative crystallinity, dimethyl ether conversion rate and mechanical strength of the samples all show a gradual upward trend. It is particularly worth noting that only 3 h of crystallization (Example 15) is required for the dimethyl ether conversion rate of the obtained catalyst to exceed that of the powder catalyst (Comparative Example 4); when the crystallization time is extended to 12 h (Example 16), its mechanical strength can exceed that of the traditional industrial shaped catalyst (Comparative Example 5). These results show that the present process can prepare a fully crystalline mordenite shaped catalyst with excellent catalytic performance and sufficient mechanical strength in a relatively short crystallization time, exhibiting a significant time efficiency advantage and providing strong technical support for industrial application.
[0057] Table 6 Relative crystallinity, catalytic performance of dimethyl ether carbonylation reaction and mechanical strength of samples with different crystallization times
[0058] The remaining matters of the present application are known technologies.
Claims
1. A fully crystalline mordenite zeolite molding catalyst, characterized in that, The catalyst is composed entirely of mordenite crystals, without any other crystalline or amorphous components, and has a mechanical strength of 60~300 N / cm. It is shaped as one of the following: spherical, strip-shaped, clover-shaped, cylindrical with a central hole, or clover-shaped; with a diameter of 1~5 mm and a length of 1~10 mm.
2. The preparation method of the fully crystalline mordenite zeolite forming catalyst as described in claim 1, characterized in that, Includes the following steps: (1) Mix silicon source, aluminum source, alkali source and water to form a white colloid, then mix it with mordenite molecular sieve and shape it to obtain catalyst precursor; The molar ratio of silicon source, aluminum source, alkali source and water is 1:(0.025~0.25):(0.05~0.5):(5~30); the molecular sieve content is 50~90 wt% of the total mass of the precursor; the molar amount of silicon source is calculated as silicon dioxide. The silicon source is selected from one or more of silica sol, sodium silicate, and water glass; the aluminum source is selected from one or more of aluminum sulfate, aluminum nitrate, and sodium aluminate; the alkali source is sodium hydroxide; and the molecular sieve is selected from mordenite. (2) The catalyst precursor is loaded onto the grid in the crystallization kettle, water is added to the bottom and then sealed. The crystallization is carried out at 150~200 ℃ for 0.5~72 h with steam assistance. After crystallization, the catalyst is washed, dried and calcined to obtain Na-type mordenite zeolite shaped catalyst. The mass ratio of catalyst precursor to water is 1:1 to 1:
5. (3) The Na-type mordenite zeolite molding catalyst was immersed in an ammonium salt solution. After ammonium ion exchange, it was filtered, washed, dried, and calcined in an air atmosphere at 400~600 ℃ for 3~8 h to obtain the hydrogen-type fully crystalline mordenite zeolite molding catalyst. The ammonium salt is one or more of ammonium nitrate, ammonium chloride, ammonium carbonate, and ammonium sulfate, with an ammonium salt concentration of 0.1~1 mol / L; the exchange temperature is room temperature to 80 ℃, and the exchange time is 1~8 h.
3. The preparation method of the fully crystalline mordenite zeolite forming catalyst as described in claim 2, characterized in that, The catalyst precursor in step (1) has a diameter of 1~5 mm and a length of 1~10 mm.
4. The preparation method of the fully crystalline mordenite zeolite forming catalyst as described in claim 2, characterized in that... Molecular sieve powder is mixed with silicon, aluminum and alkali sources, and then the mixture is produced by one of extrusion molding, tableting or spray molding, controlling the specified shape and particle size, and supplemented by drying or breaking steps to obtain a catalyst precursor.
5. The preparation method of the fully crystalline mordenite zeolite forming catalyst as described in claim 2, characterized in that, In step (2), the crystallized solid is washed until pH < 9, dried, and then calcined in air at 500~600 ℃ for 3~8 h.
6. The application of the fully crystalline mordenite zeolite forming catalyst as described in claim 1, characterized in that, It is used for the carbonylation of dimethyl ether to synthesize methyl acetate or the carbonylation of methanol to synthesize acetic acid.
7. The application of the fully crystalline mordenite zeolite forming catalyst as described in claim 6, characterized in that, Includes the following steps: The feed gas, carbon monoxide, and auxiliary gas are introduced into a fixed-bed reactor at 180–260 °C, a pressure of 1.0–5.0 MPa, and a total space velocity of 1500–12000 h⁻¹. -1 Under the given conditions, the product is obtained; the raw material is dimethyl ether or methanol. The molar fraction of each component in the total material is: 2~20% raw material gas, 60~98% carbon monoxide, and 0~20% auxiliary gas; When the raw material is dimethyl ether, the product is methyl acetate; when the raw material is methanol, the product is acetic acid. The auxiliary gas is hydrogen or an inert gas; the inert gas is nitrogen, argon or helium.
Citation Information
Patent Citations
Preparation method of binder-free mordenite zeolite
CN105366688B
Preparation method of full-crystalline MOR molecular sieve
CN118320854A